Motor and morphological differences between young female handball players from three age groups - Mohoric, U.; Šibila, M.; Bon, M. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2021)
The study aimed to establish whether any statistically significant differences exist between three age categories of elite young Slovenian female handball players in terms of the results achieved in some motor and morphological parameters. For this purpose, members of the Slovenian female national team born in 1998/99 and 2000/2001 were selected so that their average respective age was 15, 17 and 19 years. The set of motor measures included 12 parameters covering various motor areas relevant to handball. The measures defining the subjects' morphological status included 8 parameters or appropriately calculated indices (Šibila and Pori, 2009). The number of subjects differed each year, although all three measurements were carried out with the 29 subjects included in our study. All measurements were conducted by the same people, using the same measurement technology. The results were processed with descriptive statistics methods and the differences between the groups were established using a Kruskal-Wallis test. The results showed that statistically significant differences between young female handball players aged 15, 17 and 19 could not be confirmed in the most of the studied parameters. Obviously, 15 is the age at which those female players who were included by their coaches among the ranks of talented national team players have reached their biological maturity in morphological and motor terms. The majority of morphological characteristics and motor abilities are highly genetically conditioned. Thus, only statistically significant differences were established between players older than 15 years in terms of amount of muscle mass, somatotype, 5 m and 10 m sprint time and 30-15IFT test. Evidently, the training factors do not provide a sufficiently strong stimulus for the development of other motor abilities.